Cardiovascular Health Risk Behavior Among Undergraduate Students of Purbanchal University School of Health Sciences, Morang, Nepal - Shrestha, Menuka; Subba, Dipti; Koirala, Namu; Parajuli, Surya Bahadur; Pradhan, Uma (Journal of Nursing Education of Nepal, 2023)
Introduction: Cardiovascular diseases (CVDs) are listed as one of the main causes of mortality and morbidity. Lifestyle-related behavioral risk factors are mainly implicated in the increased burden of cardiovascular diseases. The study aims to assess the cardiovascular health risk behavior among undergraduate students. Methods: A descriptive cross-sectional study was conducted from March to August 2020 among 180 undergraduate university students. Data was collected online through a web link using an edited WHO-NCD stepwise approach questionnaire and analyzed using SPSS. Ethical clearance was obtained from the IRC of Purbanchal University School of Health Sciences. Results: The majority (96.7%) of respondents were female, nearly half (47.2%) were from nursing, and most (81.7%) were unmarried and had a single family (76.7%). Among them, 5.4% were occasional smokers. Most (72.2%) of the students started to consume alcohol. Although 81% of them thought that lowering salt intake in their diet was very important, 74.4% of students often eat processed foods high in salt. Almost all (95%) of students said that extra salt or salty sauce in their diet could cause health problems. However 65% of them were not doing anything regularly to control salt intake, and 77% of the students did not practice any physical exercise. Few (5.6%) and (2.2%) students had raised blood pressure and total cholesterol levels, respectively. Conclusion: The undergraduate students have insufficient physical activity, inadequate fruit intake, and use of high levels of salt and salty products. Therefore, intervention is required to reduce these high-risk behaviors, related to cardiovascular diseases in the future. DOI: https://doi.org/10.62143/8e82yh78